Hard photon production and matrix-element parton-shower merging - Höche, Stefan; Schumann, Steffen; Siegert, Frank (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We present a Monte Carlo approach to prompt-photon production, where photons and QCD partons are treated democratically. The photon fragmentation function is modeled by an interleaved QCD+QED parton shower. This known technique is improved by including higher-order real-emission matrix elements. To this end, we extend a recently proposed algorithm for merging matrix elements and truncated parton showers. We exemplify the quality of the Monte Carlo predictions by comparing them to measurements of the photon fragmentation function at LEP and to measurements of prompt photon and diphoton production from the Tevatron experiments.